Identification and characterization of two putative novel genera of arteriviruses in shrews and rats - Wang, Xiu; Gong, Huanyu; Chen, Ruixu; Tan, Sumei; Shao, Jianwei; Chen, Jiming; Lu, Shousheng; Liao, Ming (Frontiers in Microbiology, 2025)
IntroductionCertain arteriviruses causing severe diseases in domestic animals, such as porcine respiratory and reproductive syndrome viruses, could originate through viral spillover, and simian arteriviruses pose threats to public health through viral spillover. To prepare for the spillover risks, it is desirable to delve into the diversity, evolution, and potential pathogenicity of arteriviruses in non-human primates, shrews, and rats, which are close in phylogenetics to humans or share the same habitats with humans and domestic animals.MethodsIn this study, a variety of viruses in Asian house shrews (Suncus murinus) and brown rats (Rattus norvegicus) were detected using high-throughput sequencing and virome analysis.ResultsTwo viruses were identified as novel genera in the family Arteriviridae according to the demarcation criterion of the International Committee on Taxonomy of Viruses. The two novel arteriviruses contained arterivirus-typical genomic structures, and they were different from classified arteriviruses in the N-linked glycosylation sites of their glycoproteins. Frameshift mutations, rather than genomic recombination, played a crucial role in the genetic divergence of the two viruses.DiscussionThese results expand the knowledge about the genetic diversity and evolution of shrew viruses, rodent viruses, and arteriviruses. They provide scientific data for controlling the risks posed by shrew viruses and rodent viruses to humans and livestock.